Effect of Microwave Processing and Glass Inclusions on Thermoelectric Properties of P-Type Bismuth Antimony Telluride Alloys for Wearable Applications - Amin Nozariasbmarz; Daryoosh Vashaee (Energies, 2020)
Depending on the application of bismuth telluride thermoelectric materials in cooling, waste heat recovery, or wearable electronics, their material properties, and geometrical dimensions should be designed to optimize their performance. Recently, thermoelectric materials have gained a lot of interest in wearable electronic devices for body heat harvesting and cooling purposes. For efficient wearable electronic devices, thermoelectric materials with optimum properties, i.e., low thermal conductivity, high Seebeck coefficient, and high thermoelectric figure-of-merit (zT) at room temperature, are demanded. In this paper, we investigate the effect of glass inclusion, microwave processing, and annealing on the synthesis of high-performance p-type (BixSb1−x)2Te3 nanocomposites, optimized specially for body heat harvesting and body cooling applications. Our results show that glass inclusion could enhance the room temperature Seebeck coefficient by more than 10% while maintaining zT the same. Moreover, the combination of microwave radiation and post-annealing enables a 25% enhancement of zT at room temperature. A thermoelectric generator wristband, made of the developed materials, generates 300 μW power and 323 mV voltage when connected to the human body. Consequently, MW processing provides a new and effective way of synthesizing p-type (BixSb1−x)2Te3 alloys with optimum transport properties.